2001
DOI: 10.4049/jimmunol.166.10.6266
|View full text |Cite
|
Sign up to set email alerts
|

Extrafollicular Plasmablast B Cells Play a Key Role in Carrying Retroviral Infection to Peripheral Organs

Abstract: B cells can either differentiate in germinal centers or in extrafollicular compartments of secondary lymphoid organs. Here we show the migration properties of B cells after differentiation in murine peripheral lymph node infected with mouse mammary tumor virus. Naive B cells become activated, infected, and carry integrated retroviral DNA sequences. After production of a retroviral superantigen, the infected B cells receive cognate T cell help and differentiate along the two main differentiation pathways analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 69 publications
2
36
0
Order By: Relevance
“…Several studies have clearly demonstrated that MMTV is transported to the mammary gland by lymphocytes and that infected B and T cells can release MMTV particles (6)(7)(8)(9). Because removal of the draining LN after virus infection abolished the neutralizing Ab responses, we were able to address the viral spread to lymphoid and nonlymphoid compartments in the absence of neutralizing Abs.…”
Section: Viral Infection and Tumor Development In The Absence Of Neutmentioning
confidence: 76%
See 2 more Smart Citations
“…Several studies have clearly demonstrated that MMTV is transported to the mammary gland by lymphocytes and that infected B and T cells can release MMTV particles (6)(7)(8)(9). Because removal of the draining LN after virus infection abolished the neutralizing Ab responses, we were able to address the viral spread to lymphoid and nonlymphoid compartments in the absence of neutralizing Abs.…”
Section: Viral Infection and Tumor Development In The Absence Of Neutmentioning
confidence: 76%
“…To study whether the chronic GC response in the draining LN plays a role in maintaining virus-neutralizing Ab responses and͞or viral infection we removed the draining popliteal LN after installation of a systemic infection. Day 4 after footpad injection is the peak of the extrafollicular B cell response when infected plasmablast B cells exit the draining LN and home to peripheral tissues (9). GC are initiated by days 9-10, and by day 23 a chronic GC response in the draining LN is established.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Important knowledge has been obtained by utilization of the adult mouse infection model (Ardavin et al, 1999). By using that model, it has been shown that infected B cells differentiate into IgG-secreting plasma cells (Held et al, 1993) and that B220 low cells are able to carry the virus to other organs, including mammary glands (Finke et al, 2001). However, it is unlikely that the same events take place during MMTV natural infection because the virus enters through the GALT, a mucosal tissue where B cells are very prone to switching to IgA (Butcher et al, 1982;Weisz-Carrington et al, 1977).…”
Section: Mmtv Infection Causes Increases In Pp Igamentioning
confidence: 99%
“…DNA extracted from cells of different origins was analyzed by PCR as described previously (16). In brief, 50 ng of DNA isolated from LNs, spleens, and mammary glands was analyzed by PCR with specific primers for exogenous MMTV SW. Primers for Mtv-6, -8, and -9 were used as positive controls.…”
Section: Methodsmentioning
confidence: 99%